THE PSYCHOLOGICAL ASPECT OF MAIN AND SECONDARY CHARACTERS IN THE MOVIE HOW TO TRAIN YOUR DRAGON 2 - Wangsa, I Gusti Agung Wira (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThe title of this study is The Psychological Aspect Of Main and Secondary Character In TheMovie How to Train Your Dragon 2 (2014). How to Train Your Dragon 2 premiered at the 2014Cannes Film Festival on May 16, 2014, and was released in the United States on June 13. Thismovie was launched by DreamWorks Animation and distributed by 20th Century Fox. How toTrain Your Dragon 2 is an interesting movie with Exciting, emotionally resonant, and beautifullyanimated story. The discussion of this study focussed on the topic psychological analysis. Thepsychological analysis focuses only on psychological aspect of main and secondary character andthe conflict experienced together with problems of main and secondary character. According toWilliam Kenney (1966:5) states that there are two types of conflicts and they are external andinternal conflict. Internal conflict is mostly occurs within a single man or conflict between an ideaand another. The definition of psychological aspect through the conflict is analyzed based on thetheory proposed by Bernhardt (1953) who divides the psychological aspect into want, emotions,and feelings. This study will be collected by documentation method. The data collection will betaken from the movie. The data will be collected by watching and understanding the movie andrelate to the topic. Listen the dialogue carefully and read the movie scripts reapetedly. Afterward,finding the statement relate to the psychological and conflict of the Hiccup as the main character.This study result brought some conclusions. The conflict of the main character could becategorized into two general types of the conflict: internal and external conflict arise betweenHiccup the protagoinst against Drago Bludvist the main antagonist of How To Train Your Dragon2. Drago Bludvist is a cruel, ruthless, twisted man whose main goal is to conquer the world withhis enormous army of both humans and dragons, he is feared by all and destroys anyone who getsin his way. Pyschological aspect means anything that relate to the psychological condition of thecharacter as the inside things in human being , for instance ; ego, temperament, mentality,ambition, frustration, attitude, qualities, abilities, etc. It deals with the personal qualities whichrelated with a character behavior and activites of human being as a reflection of psychological life.The psychology of main character can be analyzed through mentality, manner, feeling,imagination, thought, sense, etc. Therefore, the effect of literature an influence upon its readers oraudience psychology. Psychology discovers the stream of consciousness as the real of reproductionof the actual mental processes for the mind.The analysis of psychological aspect of main characterdivides into five classes of human motive those are: the appetites, the wants, the emotion, andsocial movies.Keywords : Psychological, Character, and MotivationABSTRAKJudul penelitian ini adalah Aspek Psikologis Karakter Utama dan Sekunder Dalam Film How toTrain Your Dragon 2 (2014). How to Train Your Dragon 2 tayang perdana di Festival FilmCannes 2014 pada 16 Mei 2014, dan dirilis di Amerika Serikat pada 13 Juni. Film ini diluncurkanoleh DreamWorks Animation dan didistribusikan oleh 20th Century Fox. How to Train YourDragon 2 adalah film menarik dengan cerita animasi yang seru, bergema secara emosional, danindah. Pembahasan penelitian ini difokuskan pada topik analisis psikologi. Analisis psikologishanya berfokus pada aspek psikologis karakter utama dan sekunder dan konflik yang dialamibersama dengan masalah karakter utama dan sekunder. Menurut William Kenney (1966:5)menyatakan bahwa ada dua jenis konflik yaitu konflik eksternal dan konflik internal. Konflikinternal sebagian besar terjadi dalam satu orang atau konflik antara ide dan ide lainnya. Definisiaspek psikologis melalui konflik dianalisis berdasarkan teori yang dikemukakan oleh Bernhardt(1953) yang membagi aspek psikologis menjadi keinginan, emosi, dan perasaan. Penelitian iniakan dikumpulkan dengan metode dokumentasi. Pengumpulan data akan diambil dari film. Dataakan dikumpulkan dengan menonton dan memahami film dan berhubungan dengan topik.Dengarkan dialognya dengan seksama dan baca kembali naskah filmnya. Setelah itu, ditemukanpernyataan yang berkaitan dengan psikologis dan konflik Hiccup sebagai tokoh utama. Hasilpenelitian ini membawa beberapa kesimpulan. Konflik karakter utama dapat dikategorikanmenjadi dua jenis umum konflik: konflik internal dan eksternal muncul antara Hiccup protagonismelawan Drago Bludvist antagonis utama How To Train Your Dragon 2. Drago Bludvist adalahpria yang kejam, kejam, bengkok yang tujuan utamanya adalah menaklukkan dunia denganpasukan besar manusia dan naga, dia ditakuti oleh semua orang dan menghancurkan siapa sajayang menghalangi jalannya. Aspek psikologis berarti segala sesuatu yang berhubungan dengankondisi psikologis karakter sebagai hal-hal yang ada di dalam diri manusia, misalnya; ego,temperamen, mentalitas, ambisi, frustrasi, sikap, kualitas, kemampuan, dll. Ini berkaitan dengankualitas pribadi yang terkait dengan perilaku karakter dan aktivitas manusia sebagai cerminankehidupan psikologis. Psikologi tokoh utama dapat dianalisis melalui mentalitas, sikap, perasaan,imajinasi, pemikiran, rasa, dll. Oleh karena itu, pengaruh sastra mempengaruhi psikologipembaca atau penontonnya. Psikologi menemukan aliran kesadaran sebagai reproduksi nyatadari proses mental yang sebenarnya untuk pikiran. Analisis aspek psikologis karakter utamamembagi menjadi lima kelas motif manusia yaitu: perasaan, keinginan, emosi, dan sosial.Kata Kunci : Psikiologi, Konflik, dan karakter